Parents as victims of rebellious children, and children who suffer from Tourette Syndrome - Pretorius, Ronelle (Koers, 1994)
Abused parents are the forgotten victims of family violence. This paper reports on the victimisation of 50 parents who are members of a lay support group, "Parents of Rebellious Children" (PORCH). Although it was not the aim of this study to investigate the role that TS could possibly play, it was a serendipity finding that TS may be a contributing factor in the rebelliousness exhibited by some children. These parents did not only experience severe verbal and physical abuse but also suffered serious damage to property at the hands of their violent children. They were often blamed if they spoke of their plight and received little moral support. Abused parents need to be recognized and treated as victims of violence. Eleven rebellious children who were treated for TS with psychotropic drugs, showed dramatic behavioural changes and the implications of such treatment are also indicated.